Transgenic rat model of neurodegeneration caused by mutation in the TDP gene. - Hongxia Zhou; Cao Huang; Han Chen; Dian Wang; Carlisle P Landel; Pedro Yuxing Xia; Robert Bowser; Yong-Jian Liu; Xu Gang Xia (PLoS Genetics)
TDP-43 proteinopathies have been observed in a wide range of neurodegenerative diseases. Mutations in the gene encoding TDP-43 (i.e., TDP) have been identified in amyotrophic lateral sclerosis (ALS) and in frontotemporal lobe degeneration associated with motor neuron disease. To study the consequences of TDP mutation in an intact system, we created transgenic rats expressing normal human TDP or a mutant form of human TDP with a M337V substitution. Overexpression of mutant, but not normal, TDP caused widespread neurodegeneration that predominantly affected the motor system. TDP mutation reproduced ALS phenotypes in transgenic rats, as seen by progressive degeneration of motor neurons and denervation atrophy of skeletal muscles. This robust rat model also recapitulated features of TDP-43 proteinopathies including the formation of TDP-43 inclusions, cytoplasmic localization of phosphorylated TDP-43, and fragmentation of TDP-43 protein. TDP transgenic rats will be useful for deciphering the mechanisms underlying TDP-43-related neurodegenerative diseases.